Literatur Review: Intervensi pada Remaja Perempuan 8000 Hari Pertama Kehidupan (HPK) sebagai Upaya Pencegahan Stunting pada Generasi di Masa Depan: Literature Review: Intervention on Adolescent Girls in 8000 First Days of Life (HPK) as Stunting Prevention in Future Generations - Brigitte Sarah Renyoet; Dary Dary; Christantya Vita Rena Nugroho (Amerta Nutrition, 2023)
Background: The complex nutrition problem until now in Indonesia is stunting. Stunting is a failure-to-grow condition due to prolonged malnutrition since the baby was born during pregnancy. Therefore, the nutrition and health of adolescent girls as the future mother have a crucial role in preventing stunting. Objectives: Identified various programs intervention to adolescent girls as stunting prevention to the next generation and identify the successful various programs intervention to adolescent girls as stunting prevention to next generation Discussion: This research method used a literature review of ten journals from 2011 to 2021. The research results were various interventions for adolescent girls as stunting prevention for the next generation. There were nutrition education, stunting education, early marriage education, hygiene and sanitation education, fulfillment of micronutrient intake and consumption of balanced food, Multi Micro Nutrient (MMN) supplementation, school feeding program, and high calcium milk intake. Intervention for adolescent girls is the main target of 8000 HPK programs as holistic stunting prevention has a vital role, so it needs to be implemented as early as possible. Conclusions: Appropriate Interventions for adolescent girls have the potential to reduce stunting and increase the opportunity for human resources in the future.